Innovative Strategy for Strengthening Institutions and Technology in the Implementation of E-Market Retribution to Increase Transparency and Accountability in Blitar Regency - Prasjakti Eka Parmana; Ulul Albab; Fedianty Agustinah; Chems Eddine Boukhedimi (International Journal of Social Science and Humanity, 2025)
This study examines innovative strategies to strengthen institutional and technological aspects of implementing the e-market retribution system to enhance transparency and accountability in Blitar Regency, East Java, Indonesia. The research employs a qualitative case study approach, utilising in-depth interviews with key informants from the Department of Trade, market managers, traders, and stakeholders, along with secondary data from official documents. The theoretical framework integrates New Public Management, Technology Acceptance Model, and Good Governance principles. Findings reveal that e-market retribution implementation faces both opportunities and challenges in institutional strengthening and technology adoption. Innovative strategies developed include: institutional restructuring through clear role division; capacity-building programs for human resources; technological integration through QRIS digital payment systems; stakeholder engagement through participatory approaches; and monitoring and evaluation mechanisms to ensure accountability. The study concludes that successful implementation requires a comprehensive approach combining institutional strengthening, technological readiness, and stakeholder collaboration. This research contributes to the literature on digital transformation in local government revenue management and provides practical recommendations for regions implementing similar innovations